A survey on computer hardware awareness of UP BLIS students - Mendoza, Richard F.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
Information technology explosion is the trend today and no one can stop this phenomena. In the field of librarianship our institution is adapting to computerization. Library services are computer-based and some UP BLIS courses use computers. This was the basis of the researcher for this study.
In this study, survey questionnaires were given at the UP BLIS students to be able to get the data. The questions raised were based on four components that answer: (1) level of awareness of UP BLIS students in terms of computer hardware (2) students' sources of computer hardware skill (3) recommendation of integrating a computer hardware course to UP BLIS curriculum (4) relationship between the year level of the respondents and the level of awareness.
Results shows 54 or (30.68 percent), juniors with 46 (26.14 percent), and 29 (16.48 percent) are freshmen. Majority of the respondents' state that they acquire the computer hardware skills at home (128), followed by the statement "thru classroom" (111) and "thru computer shops/rentals" (107). In terms of how the respondents acquire their computer hardware skill, majority of the respondents (125) acquired it "thru teaching of an individual", followed by "thru reading materials" 125), "class sessions/lectures" (104). Majority of the respondents have computers (115) while 61 don't have computers.
Almost all the respondents have a high level of knowledge regarding the following computer hardware: printer, keyboard/mouse and monitor, based on the computation of mean. Moderate level of knowledge among other respondents shows the following computer hardware parts; CD-ROM, 1.44 floppy disk drive, sound card, video card, hard disk, MODEM and drivers. The parts of the computer that the other respondents have low level of knowledge are the processor, 64mb/128mb SDRAM, PCI slot, ISA slot, AGP slot, parallel port, serial port, BIOS, USB LAN card, and PS/2.Chi-square was used to test the relevance of the dependent and independent variables.
Results show that following computer hardware are not significantly related to the year level of the respondents: 1.44 floppy disk drives, 64mb/128mb SDRAM, PCI slot, ISA slot, AGP slot, parallel port, serial port, BIOS, USB, LAN card, PS/2, CD-ROM drive, video card, sound card, hard dusk, drivers, printer, MODEM, keyboard and mouse. And the following computer hardware that are significantly related to the year level of the respondents are the processor and monitor. Further investigation is needed for additional research support in inclusion of a separate computer hardware course elective in the UP BLIS curriculum.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Human -- Computer interaction